Lithium iron phosphate positive electrode material, preparation method and application thereof
Patent Information
- Application Number
- CN202410847606.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-27
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2044-06-27
AI Technical Summary
Among the existing methods for preparing lithium iron phosphate cathode materials, the solid-phase method suffers from uneven raw material distribution and poor batch consistency, while the liquid-phase method has high equipment costs and low compaction density, making it difficult to simultaneously achieve high compaction density and phase uniformity.
A preparation method combining liquid-phase and solid-phase methods is adopted. By mechanically grinding solid-phase raw materials and liquid-phase precursors, lithium iron phosphate with a variety of particle sizes is generated by using different reaction rates. This enables the preparation of high-density and homogeneous materials through a single sintering process.
This method enables the low-cost preparation of high-performance lithium iron phosphate cathode materials, combining the advantages of high consistency from liquid-phase methods and simple equipment from solid-phase methods. It improves the compaction density and production efficiency of the materials while retaining good carbon coating effects.
Smart Images

Figure CN118619237B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of battery technology and relates to a lithium iron phosphate cathode material, its preparation method and application. Background Technology
[0002] Lithium-ion batteries, with their high voltage, high energy density, and good cycle performance, have become one of the most widely used chemical energy storage devices. In recent years, lithium iron phosphate batteries have been widely used in the field of power batteries due to their cost and safety advantages.
[0003] Lithium iron phosphate (LFP) is the most commercially successful phosphate-based cathode material, but its low energy density is also a drawback. The discharge capacity of LFP materials on the market has approached the theoretical value and is difficult to improve, but there is still much room for improvement in the material's compaction density. Existing technologies for preparing LFP can be broadly divided into two categories: solid-phase and liquid-phase methods. Solid-phase methods have simple equipment and processes, and the preparation conditions are easy to control. However, their disadvantages include uneven solid phase of raw materials, a wide particle size distribution range, and poor batch-to-batch consistency. Liquid-phase methods allow for easy control of crystal form and particle size, resulting in a homogeneous phase, but the process is complex and the equipment cost is high.
[0004] Solid-phase methods can improve compaction density by using sand milling to achieve particle size matching. For example, patent CN109795998A discloses a preparation method for improving the compaction density of lithium iron phosphate cathode material and lithium iron phosphate cathode material. The method involves mixing slurries of particles of different sizes after grinding, drying, and sintering to obtain the finished product. In contrast, liquid-phase methods, where crystals grow uniformly in a solvent, cannot control particle size through sand milling. Materials prepared by liquid-phase methods typically have lower compaction densities.
[0005] Based on the above research, there is a need to provide a method for preparing lithium iron phosphate cathode materials that overcomes the defects of solid-phase and liquid-phase preparation, and can obtain high-pressure lithium iron phosphate cathode materials with uniform phase. Summary of the Invention
[0006] The purpose of this invention is to provide a lithium iron phosphate cathode material, its preparation method, and its application. The preparation method is an incomplete liquid phase method, which combines liquid phase and solid phase methods to achieve a high-density lithium iron phosphate cathode material with a uniform particle size distribution and phase uniformity in a single sintering process.
[0007] To achieve this objective, the present invention adopts the following technical solution:
[0008] In a first aspect, the present invention provides a method for preparing a lithium iron phosphate cathode material, the method comprising the following steps:
[0009] (1) The solid-phase raw material and the dispersion medium are mechanically ground to obtain the first slurry;
[0010] The raw materials for the solid-phase method include iron, phosphorus, and lithium sources;
[0011] (2) Mix the liquid phase raw material with the solvent to obtain a second slurry, and mix the second slurry with the first slurry in step (1) to obtain a third slurry;
[0012] The raw materials for the liquid phase method include iron, phosphorus, and lithium sources; the first slurry and the second slurry have different compositions;
[0013] (3) The third slurry described in step (2) is dried and sintered to obtain the lithium iron phosphate cathode material.
[0014] This invention utilizes a combination of solid-phase and liquid-phase methods for preparation. Since the precursor prepared by the liquid-phase method in step (2) has a different material composition than the product of mechanical grinding of the raw material in the solid-phase method in step (1), the growth rate of lithium iron phosphate crystals differs due to the difference in reaction rates of different substances during the sintering process of the obtained composite precursor. This results in the generation of spherical small-particle lithium iron phosphate generated by the liquid-phase precursor, which fills the voids in the spherical large-particle lithium iron phosphate generated by the mechanical grinding product of the solid-phase method. This allows the material to combine the high consistency of the liquid-phase method with the advantages of the simple equipment and process of the solid-phase method, thus achieving low-cost preparation of high-performance lithium iron phosphate.
[0015] Preferably, the mass of lithium iron phosphate generated from the solid-phase raw material in step (1) accounts for 5%-15% of the total mass of the lithium iron phosphate cathode material. For example, it can be 5%, 10% or 15%, but it is not limited to the listed values. Other unlisted values within the range are also applicable.
[0016] The lithium iron phosphate produced by the solid-phase method of this invention consists of large particles, while the lithium iron phosphate produced by the liquid-phase method consists of small particles. The proportion of lithium iron phosphate produced by the two methods in the finished product affects the proportion of large and small particles. Therefore, by adjusting the proportion of raw materials, the proportion of large particles in the finished product can be adjusted. The mass proportion of lithium iron phosphate produced by the solid-phase method and the mass proportion of lithium iron phosphate produced by the liquid-phase method of this invention are coordinated to prepare high-pressure lithium iron phosphate cathode materials.
[0017] Preferably, the mechanical grinding method in step (1) includes sand grinding.
[0018] Preferably, the mechanical grinding in step (1) results in a particle size D50 of 1.2-1.8 μm, for example, 1.2 μm, 1.4 μm, 1.6 μm or 1.8 μm, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0019] Preferably, in step (1), the solid-phase raw material and the dispersion medium are first stirred and dispersed to obtain a slurry with a solid content of 40wt%-60wt%, for example, 40wt%, 50wt% or 60wt%, and then mechanically ground.
[0020] Preferably, an organic carbon source is added during the mechanical grinding in step (1).
[0021] This invention retains the highly uniform mixing of organic carbon sources achieved by wet grinding in the solid-phase method. Therefore, by adding an organic carbon source to the solid-phase method, the finished product has a good carbon coating effect and higher production efficiency, with a higher phase homogeneity than that of the simple solid-phase method.
[0022] Preferably, the organic carbon source includes any one or a combination of at least two of glucose, sucrose, citric acid, or polyethylene glycol;
[0023] Preferably, the amount of organic carbon source added is 8wt%-14wt% of the theoretical amount of pure phase lithium iron phosphate to be generated, for example, it can be 8wt%, 10wt%, 12wt% or 14wt%, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0024] The theoretical amount of pure-phase lithium iron phosphate produced in this invention is calculated based on the amount of lithium iron phosphate raw material.
[0025] Preferably, a dopant is added during the mechanical grinding process described in step (1).
[0026] Similarly, in this invention, a dopant is added to the solid-state method in step (1) to make the doping more uniform.
[0027] Preferably, the dopant includes any one or a combination of at least two of titanium dioxide, magnesium oxide, or vanadium pentoxide.
[0028] Preferably, the amount of dopant added is 2wt‰-5wt‰ of the theoretical amount of pure phase lithium iron phosphate to be generated. For example, it can be 2wt‰, 3wt‰, 4wt‰ or 5wt‰, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0029] Preferably, the iron, phosphorus and lithium sources in the solid-phase raw materials described in step (1) do not react with the dispersion medium during mechanical grinding.
[0030] In step (1) of the present invention, solid-phase mixing is performed, wherein the dispersion medium is used as the medium during mechanical grinding. The iron source, phosphorus source and lithium source in the solid-phase raw material do not react with the dispersion medium to generate lithium iron phosphate during mechanical grinding, but react in the subsequent sintering process, so that the composition of the material obtained by the liquid phase method in step (2) is different from that obtained by the solid phase method in step (1), and different growth rates are achieved in the subsequent sintering process.
[0031] Preferably, the iron source in the solid-phase raw material in step (1) includes any one or a combination of at least two of ferric phosphate, ferrous oxalate, or ferric oxide.
[0032] Preferably, the phosphorus source in the solid-phase raw material in step (1) includes any one or a combination of at least two of phosphoric acid, iron phosphate, diammonium hydrogen phosphate or diammonium dihydrogen phosphate.
[0033] Preferably, the lithium source in the solid-phase raw material in step (1) includes lithium carbonate and / or lithium hydroxide.
[0034] Preferably, the dispersion medium in step (1) includes deionized water.
[0035] Preferably, in the solid-phase raw material described in step (1), the molar ratio of iron, phosphorus and lithium is (0.97-0.99):1:(1.01-1.04), for example, it can be 0.97:1:1.01, 0.98:1:1.02 or 0.99:1:1.04, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0036] Preferably, the mass of lithium iron phosphate generated from the liquid phase raw material in step (2) accounts for 85%-95% of the total mass of the lithium iron phosphate cathode material. For example, it can be 85%, 90% or 95%, but it is not limited to the listed values. Other unlisted values within the range are also applicable.
[0037] Preferably, the iron source, phosphorus source and lithium source in the liquid phase raw material in step (2) react when mixed with the solvent.
[0038] In step (2) of this invention, the raw materials of the liquid phase method are mixed with the solvent to obtain the second slurry. During the preparation process of the liquid phase method, a preliminary reaction will occur during mixing, and the composition of the material is different from that obtained by mechanical grinding in the solid phase method.
[0039] Preferably, the iron source in the liquid phase raw material in step (2) includes any one or a combination of at least two of ferrous acetate, ferric nitrate, or ferrous sulfate.
[0040] Preferably, the phosphorus source in the liquid phase raw material in step (2) includes any one or a combination of at least two of phosphoric acid, lithium dihydrogen phosphate, diammonium hydrogen phosphate, or ammonium dihydrogen phosphate.
[0041] Preferably, the lithium source in the liquid phase raw material in step (2) includes any one or a combination of at least two of lithium carbonate, lithium hydroxide, or lithium dihydrogen phosphate.
[0042] Preferably, in the liquid phase raw material described in step (2), the molar ratio of iron, phosphorus and lithium is (0.97-0.99):1:(1.01-1.04), for example, it can be 0.97:1:1.01, 0.98:1:1.02 or 0.99:1:1.04, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0043] Preferably, the drying method in step (3) includes spray drying.
[0044] Preferably, the inlet temperature of the spray dryer is 180℃-280℃, for example, 180℃, 220℃, 250℃ or 280℃, and the outlet temperature is 80℃-110℃, for example, 80℃, 90℃, 100℃ or 110℃, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0045] Preferably, the heating rate of the sintering in step (3) is 2℃ / min-5℃ / min, for example, 2℃ / min, 4℃ / min or 5℃ / min, the temperature is 700℃-820℃, for example, 700℃, 750℃, 800℃ or 820℃, and the time is 6h-10h, for example, 6h, 8h or 10h, but not limited to the listed values. Other unlisted values within the range are also applicable.
[0046] Preferably, after sintering in step (3), the material is further crushed and sieved.
[0047] As a preferred embodiment of the preparation method of the present invention, the preparation method includes the following steps:
[0048] (1) The solid-phase raw materials, organic carbon source, dopant and dispersion medium are stirred and dispersed to obtain a slurry with a solid content of 40wt%-60wt%, and then sand milled until the particle size D50 is 1.2μm-1.8μm to obtain the first slurry;
[0049] The solid-phase raw materials include an iron source, a phosphorus source, and a lithium source, wherein the iron source and the lithium source are insoluble in the dispersion medium;
[0050] The mass of lithium iron phosphate generated from the solid-phase raw materials accounts for 5%-15% of the total mass of the lithium iron phosphate cathode material; the amount of organic carbon source added is 8wt%-14wt% of the theoretical amount of pure phase lithium iron phosphate generated; the amount of dopant added is 2wt‰-5wt‰ of the theoretical amount of pure phase lithium iron phosphate generated.
[0051] (2) After dissolving or dispersing the raw materials of the liquid phase method by stirring with a solvent, a second slurry is obtained. The first slurry of step (1) is added to the second slurry to obtain a third slurry.
[0052] The liquid-phase raw materials include an iron source, a phosphorus source, and a lithium source, wherein the iron source and the phosphorus source are dissolved in the solvent; the mass of lithium iron phosphate generated from the liquid-phase raw materials accounts for 85%-95% of the total mass of the lithium iron phosphate cathode material;
[0053] (3) The third slurry described in step (2) is spray-dried at an inlet temperature of 180℃-280℃ and an outlet temperature of 80℃-110℃ to obtain a composite precursor. The composite precursor is then heated to 700℃-820℃ under a protective gas at a heating rate of 2℃ / min-5℃ / min and sintered for 6h-10h. After cooling, crushing and sieving, the lithium iron phosphate cathode material is obtained.
[0054] In a second aspect, the present invention provides a lithium iron phosphate cathode material, which is prepared by the preparation method described in the first aspect.
[0055] Preferably, the lithium iron phosphate cathode material comprises large-particle lithium iron phosphate with a primary particle size in the range of 2μm±0.5μm and small-particle lithium iron phosphate with a primary particle size in the range of 0.8μm±0.4μm.
[0056] Preferably, the small lithium iron phosphate particles are filled in a framework constructed from large lithium iron phosphate particles.
[0057] Preferably, the content of large-particle lithium iron phosphate in the lithium iron phosphate cathode material is 5wt%-15wt%, for example, it can be 5wt%, 8wt%, 10wt%, 12wt% or 15wt%, but is not limited to the listed values. Other unlisted values within the range are also applicable.
[0058] Thirdly, the present invention provides a lithium-ion battery comprising the lithium iron phosphate cathode material as described in the second aspect.
[0059] Compared with the prior art, the present invention has the following beneficial effects:
[0060] (1) This invention combines solid-phase and liquid-phase methods to prepare high-density lithium iron phosphate cathode materials with uniform phases. The slurry obtained by mechanically grinding raw materials in the solid-phase method is mixed with the lithium iron phosphate precursor generated in the liquid-phase method. Then, the mixture is spray-dried and sintered. By utilizing the non-uniformity of crystal growth during the sintering process of different raw materials, lithium iron phosphate finished products with a combination of large and small particles are generated. This allows the material to combine the high consistency of materials prepared by the liquid-phase method with the advantages of simple equipment and processes in the solid-phase method, thus achieving low-cost preparation of high-performance lithium iron phosphate.
[0061] (2) Based on the improvement of material compaction density by combining large and small particles, this invention retains the advantages of both liquid phase method and solid phase method. While retaining the liquid phase method to ensure uniform mixing of raw materials at the molecular level and ensure the consistency of finished products, this invention has the advantages of higher compaction density of synthesized materials and higher production efficiency compared with the liquid phase method alone. This invention also retains the wet ball milling in the solid phase method to achieve highly uniform mixing of organic carbon sources, and the finished products have good carbon coating effect and higher production efficiency, with higher phase homogeneity than the solid phase method alone. Attached Figure Description
[0062] Figure 1 This is a SEM image of the lithium iron phosphate cathode material prepared in Example 1 of the present invention;
[0063] Figure 2 The XRD patterns of the lithium iron phosphate cathode material prepared in Example 1 of this invention and the standard lithium iron phosphate XRD are shown.
[0064] Figure 3 The particle size distribution curves of the lithium iron phosphate cathode materials prepared in Examples 1, 1, and 2 of this invention are shown. Detailed Implementation
[0065] The technical solution of the present invention will be further illustrated below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely illustrative of the present invention and should not be construed as limiting the invention in any way.
[0066] Example 1
[0067] This embodiment provides a method for preparing a lithium iron phosphate cathode material, the method comprising the following steps:
[0068] (1) The solid-phase raw materials, organic carbon source, dopant and dispersion medium are stirred and dispersed to obtain a slurry with a solid content of 50wt%, and then sand milled until the particle size D50 is 1.5μm to obtain the first slurry;
[0069] The solid-phase raw materials include iron, phosphorus and lithium sources that do not react during sand milling. The dispersion medium is deionized water. The iron and phosphorus sources of the solid-phase raw materials are both iron phosphate, and the lithium source is lithium carbonate. The solid-phase raw materials are weighed in a molar ratio of Fe:P:Li = 0.97:1:1.02.
[0070] The mass of lithium iron phosphate generated from the solid-phase raw materials accounts for 10% of the total mass of the lithium iron phosphate cathode material; the organic carbon source is glucose, and the amount added is 12wt% of the theoretical amount of pure phase lithium iron phosphate generated; the dopant is titanium dioxide, and the amount added is 2wt‰ of the theoretical amount of pure phase lithium iron phosphate generated.
[0071] (2) After dissolving or dispersing the raw material in the liquid phase method with deionized water, a second slurry is obtained. The first slurry in step (1) is added to the second slurry to obtain a third slurry.
[0072] The liquid-phase raw materials include an iron source, a phosphorus source, and a lithium source that react during the preparation of the second slurry. The iron source, phosphorus source, and lithium source are dissolved in deionized water. Specifically, the iron source in the liquid-phase raw materials is ferrous acetate, the phosphorus source is phosphoric acid, and the lithium source is lithium hydroxide. The liquid-phase raw materials are weighed in a molar ratio of Fe:P:Li = 0.97:1:1.02. The mass of lithium iron phosphate generated from the liquid-phase raw materials accounts for 90% of the total mass of the lithium iron phosphate cathode material.
[0073] (3) The third slurry described in step (2) is spray-dried. The inlet temperature of the spray dryer is 220°C, the outlet temperature is 90°C, and the compressed air pressure is 0.4MPa to obtain a composite precursor. Then, the composite precursor is heated to 780°C at a heating rate of 5°C / min under nitrogen protection and sintered for 8 hours. After naturally cooling to below 80°C, the material is taken out and crushed by airflow pulverization. The crushed material is screened through a 200-mesh sieve. The material on the sieve is crushed again, and the material under the sieve is the lithium iron phosphate cathode material.
[0074] The lithium iron phosphate cathode material includes large lithium iron phosphate particles with a primary particle size in the range of 2μm±0.5μm and small lithium iron phosphate particles with a primary particle size in the range of 0.8μm±0.4μm. The small lithium iron phosphate particles are filled in a framework constructed from large lithium iron phosphate particles. The content of large lithium iron phosphate particles in the lithium iron phosphate cathode material is 10wt%.
[0075] The SEM image of the lithium iron phosphate cathode material obtained in this embodiment is as follows: Figure 1 As shown, by Figure 1 It can be seen that the material has a mix of large and small particles, with small particles filling the gaps between large particles; the XRD of the lithium iron phosphate cathode material obtained in this embodiment and the XRD of standard lithium iron phosphate are as follows. Figure 2 As shown, by Figure 2 It can be seen that the synthesized material highly overlaps with the standard card PDF#83-2092, indicating that the synthesized material is a pure-phase lithium iron phosphate material; the particle size distribution curve of the lithium iron phosphate cathode material obtained in this embodiment is as follows. Figure 3 As shown.
[0076] Example 2
[0077] This embodiment provides a method for preparing a lithium iron phosphate cathode material, the method comprising the following steps:
[0078] (1) The solid-phase raw materials, organic carbon source, dopant and dispersion medium are stirred and dispersed to obtain a slurry with a solid content of 60wt%, and then sand milled until the particle size D50 is 1.8μm to obtain the first slurry;
[0079] The solid-phase raw materials include iron, phosphorus, and lithium sources that do not react during sand milling. The dispersion medium is deionized water. The iron source of the solid-phase raw materials is ferrous oxalate, the phosphorus source is ammonium dihydrogen phosphate, and the lithium source is lithium carbonate. The solid-phase raw materials are weighed in a molar ratio of Fe:P:Li = 0.99:1:1.04.
[0080] The mass of lithium iron phosphate generated from the solid-phase raw materials accounts for 5% of the total mass of the lithium iron phosphate cathode material; the organic carbon source is glucose, and the amount added is 14wt% of the theoretical amount of pure phase lithium iron phosphate generated; the dopant is titanium dioxide, and the amount added is 2wt‰ of the theoretical amount of pure phase lithium iron phosphate generated.
[0081] (2) After dissolving or dispersing the raw material in the liquid phase method with deionized water, a second slurry is obtained. The first slurry in step (1) is added to the second slurry to obtain a third slurry.
[0082] The liquid-phase raw materials include an iron source, a phosphorus source, and a lithium source that react during the preparation of the second slurry. The iron source, phosphorus source, and lithium source are dissolved in deionized water. The liquid-phase iron source is ferrous acetate, the phosphorus source is phosphoric acid, and the lithium source is lithium hydroxide. The liquid-phase raw materials are weighed in a molar ratio of Fe:P:Li = 0.99:1:1.04. The mass of lithium iron phosphate generated from the liquid-phase raw materials accounts for 95% of the total mass of the lithium iron phosphate cathode material.
[0083] (3) The third slurry described in step (2) is spray-dried. The inlet temperature of the spray dryer is 280°C, the outlet temperature is 110°C, and the compressed air pressure is 0.4MPa to obtain a composite precursor. Then, the composite precursor is heated to 700°C at a heating rate of 2°C / min under nitrogen protection and sintered for 10 hours. The material is then naturally cooled to below 80°C and removed. The sintered material is crushed by mechanical grinding. The crushed material is screened through a 200-mesh sieve. The material on the sieve is crushed again, and the material under the sieve is the lithium iron phosphate cathode material.
[0084] The lithium iron phosphate cathode material comprises large lithium iron phosphate particles with a primary particle size ranging from 2μm to 0.5μm and small lithium iron phosphate particles with a primary particle size ranging from 0.8μm to 0.4μm. The small lithium iron phosphate particles are filled in a framework constructed from the large lithium iron phosphate particles. The content of the large lithium iron phosphate particles in the lithium iron phosphate cathode material is 5wt%.
[0085] Example 3
[0086] This embodiment provides a method for preparing a lithium iron phosphate cathode material, the method comprising the following steps:
[0087] (1) The solid-phase raw materials, organic carbon source, dopant and dispersion medium are stirred and dispersed to obtain a slurry with a solid content of 40wt%, and then sand milled until the particle size D50 is 1.2μm to obtain the first slurry;
[0088] The solid-phase raw materials include iron, phosphorus and lithium sources that do not react during sand milling. The dispersion medium is deionized water. The iron and phosphorus sources of the solid-phase raw materials are both iron phosphate, and the lithium source is lithium carbonate. The solid-phase raw materials are weighed in a molar ratio of Fe:P:Li = 0.97:1:1.02.
[0089] The mass of lithium iron phosphate generated from the solid-phase raw materials accounts for 15% of the total mass of the lithium iron phosphate cathode material; the organic carbon source is sucrose, and the amount added is 8 wt% of the theoretical amount of pure phase lithium iron phosphate generated; the dopant is magnesium oxide, and the amount added is 5 wt‰ of the theoretical amount of pure phase lithium iron phosphate generated.
[0090] (2) After dissolving or dispersing the raw material in the liquid phase method with deionized water, a second slurry is obtained. The first slurry in step (1) is added to the second slurry to obtain a third slurry.
[0091] The liquid-phase raw materials include an iron source, a phosphorus source, and a lithium source that react during the preparation of the second slurry. The iron source is ferrous sulfate, the phosphorus source is ammonium dihydrogen phosphate, and the lithium source is lithium carbonate. The liquid-phase raw materials are weighed in a molar ratio of Fe:P:Li = 0.97:1:1.02. The mass of lithium iron phosphate generated from the liquid-phase raw materials accounts for 85% of the total mass of the lithium iron phosphate cathode material.
[0092] (3) The third slurry described in step (2) is spray-dried. The inlet temperature of the spray dryer is 180°C, the outlet temperature is 80°C, and the compressed air pressure is 0.4MPa to obtain a composite precursor. Then, the composite precursor is heated to 820°C at a heating rate of 5°C / min under nitrogen protection and sintered for 6 hours. After naturally cooling to below 80°C, the material is taken out. The sintered material is crushed by airflow pulverization. The crushed material is screened through a 200-mesh screen. The material on the screen is crushed again, and the material under the screen is the lithium iron phosphate cathode material.
[0093] The lithium iron phosphate cathode material includes large lithium iron phosphate particles with a primary particle size in the range of 2μm±0.5μm and small lithium iron phosphate particles with a primary particle size in the range of 0.8μm±0.4μm. The small lithium iron phosphate particles are filled in a framework constructed from large lithium iron phosphate particles. The content of large lithium iron phosphate particles in the lithium iron phosphate cathode material is 15wt%.
[0094] Example 4
[0095] This embodiment provides a method for preparing lithium iron phosphate cathode material. The preparation method is the same as in Example 1, except that the mass of lithium iron phosphate generated from the solid-phase raw materials accounts for 3% of the total mass of the lithium iron phosphate cathode material, and the mass of lithium iron phosphate generated from the liquid-phase raw materials accounts for 97% of the total mass of the lithium iron phosphate cathode material.
[0096] Example 5
[0097] This embodiment provides a method for preparing lithium iron phosphate cathode material. The preparation method is the same as in Example 1, except that the mass of lithium iron phosphate generated from the solid-phase raw materials accounts for 20% of the total mass of the lithium iron phosphate cathode material, and the mass of lithium iron phosphate generated from the liquid-phase raw materials accounts for 80% of the total mass of the lithium iron phosphate cathode material.
[0098] Example 6
[0099] This embodiment provides a method for preparing lithium iron phosphate cathode material. The preparation method is the same as in Example 1, except that the mass of lithium iron phosphate generated from the solid-phase raw materials accounts for 30% of the total mass of the lithium iron phosphate cathode material, and the mass of lithium iron phosphate generated from the liquid-phase raw materials accounts for 70% of the total mass of the lithium iron phosphate cathode material.
[0100] Example 7
[0101] This embodiment provides a method for preparing lithium iron phosphate cathode material. The preparation method is the same as in Example 1, except that the organic carbon source mentioned in step (1) is dispersed together with the liquid phase raw material in deionized water in step (2) and is not added in step (1).
[0102] Example 8
[0103] This embodiment provides a method for preparing lithium iron phosphate cathode material. The preparation method is the same as in Example 1, except that the dopant mentioned in step (1) is dispersed together with the raw material in deionized water in step (2) and is not added in step (1).
[0104] Comparative Example 1
[0105] This comparative example provides a method for preparing lithium iron phosphate cathode material. The preparation method is the same as in Example 1 except that step (1) is not performed and the organic carbon source, dopant and liquid phase raw material in step (1) are dispersed together in deionized water.
[0106] The particle size distribution curve of the lithium iron phosphate cathode material obtained in this comparative example is as follows: Figure 3 As shown.
[0107] Comparative Example 2
[0108] This comparative example provides a method for preparing lithium iron phosphate cathode material. The preparation method is the same as in Example 1 except that step (2) is omitted and the first slurry obtained in step (1) is directly processed in step (3).
[0109] The particle size distribution curve of the lithium iron phosphate cathode material obtained in this comparative example is as follows: Figure 3 As shown.
[0110] Comparative Example 3
[0111] This comparative example provides a method for preparing a lithium iron phosphate cathode material, the method comprising the following steps:
[0112] The lithium iron phosphate cathode material prepared in Comparative Example 1 and the lithium iron phosphate cathode material prepared in Comparative Example 2 were mixed at a mass ratio of 9:1 to obtain the lithium iron phosphate cathode material of this comparative example.
[0113] The lithium iron phosphate cathode materials obtained in the above examples and comparative examples were subjected to compaction density testing under 3T pressure. The lithium iron phosphate cathode materials obtained in the above examples and comparative examples were prepared into cathode sheets, which were then combined with lithium sheets, polyethylene separators, and lithium hexafluorophosphate electrolyte to form batteries. The first discharge specific capacity and coulombic efficiency were tested in accordance with Appendix G of GB / T 33822-2017.
[0114] The test results are shown in Table 1:
[0115] Table 1
[0116]
[0117] As can be seen from Table 1:
[0118] As can be seen from Examples 1 and Comparative Examples 1-3, compared to the liquid-phase method of Comparative Example 1 and the solid-phase method of Comparative Example 2, the method combining the solid-phase and liquid-phase methods of this invention can retain the advantages of both, improve the compaction density and electrochemical performance of the material, and even if the products prepared by the solid-phase and liquid-phase methods are mixed again, the compaction density and electrochemical performance of the resulting material are still inferior to those of Example 1. Figure 3 It can be seen that the particle size D50 of Example 1 is between that of Comparative Example 1 and Comparative Example 2, and the particle size is moderate. As can be seen from Example 1 and Examples 4-6, the preparation of finished products by liquid phase raw materials and solid phase raw materials in a suitable ratio can achieve the combination of large and small particles to improve the compaction density of the material. If the solid phase raw materials are too high, more large particles will be generated, and the gaps cannot be completely filled, resulting in low compaction density. If fewer large particles are generated, the combination of large and small particles cannot be achieved. As can be seen from Example 1 and Examples 7-8, the organic carbon source and dopant of the present invention are preferably added during the solid phase synthesis in step (1) to ensure the coating and doping effect.
[0119] In summary, this invention provides a lithium iron phosphate cathode material, its preparation method, and its application. The preparation method is an incomplete liquid-phase method, which combines liquid-phase and solid-phase methods to achieve a high-density lithium iron phosphate cathode material with a uniform particle size distribution and phase uniformity in a single sintering process.
[0120] The above description is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention fall within the protection and disclosure scope of the present invention.
Claims
1. A method for preparing a lithium iron phosphate cathode material, characterized in that, The preparation method includes the following steps: (1) The solid-phase raw materials and the dispersion medium are mechanically ground to obtain the first slurry; The solid-phase raw materials include an iron source, a phosphorus source, and a lithium source; the iron source, phosphorus source, and lithium source in the solid-phase raw materials do not react with the dispersion medium during mechanical grinding. The iron source in the solid-phase raw material includes any one or a combination of at least two of ferric phosphate, ferrous oxalate, or ferric oxide, and the phosphorus source includes any one or a combination of at least two of ferric phosphate, diammonium hydrogen phosphate, or ammonium dihydrogen phosphate. (2) The raw materials of the liquid phase method are mixed with the solvent to obtain a second slurry. The second slurry is then mixed with the first slurry of step (1) to obtain a third slurry. The raw materials for the liquid phase method include an iron source, a phosphorus source, and a lithium source; the iron source, phosphorus source, and lithium source in the liquid phase method raw materials will react when mixed with the solvent; the first slurry and the second slurry have different compositions; The iron source in the liquid phase method raw material includes any one or a combination of at least two of ferrous acetate, ferric nitrate or ferrous sulfate, and the phosphorus source includes any one or a combination of at least two of phosphoric acid, lithium dihydrogen phosphate, diammonium hydrogen phosphate or ammonium dihydrogen phosphate. (3) The third slurry described in step (2) is dried and sintered to obtain the lithium iron phosphate cathode material.
2. The preparation method according to claim 1, characterized in that, In step (1), the mass of lithium iron phosphate generated from the solid-phase raw materials accounts for 5%-15% of the total mass of the lithium iron phosphate cathode material.
3. The preparation method according to claim 1, characterized in that, The mechanical grinding method described in step (1) includes sand grinding.
4. The preparation method according to claim 1, characterized in that, In step (1), the mechanical grinding is carried out until the particle size D50 is 1.2μm-1.8μm.
5. The preparation method according to claim 1, characterized in that, In step (1), the solid phase raw materials and dispersion medium are first stirred and dispersed to obtain a slurry with a solid content of 40wt%-60wt%, and then mechanically ground.
6. The preparation method according to claim 1, characterized in that, During the mechanical grinding process described in step (1), an organic carbon source was also added.
7. The preparation method according to claim 6, characterized in that, The organic carbon source includes any one or a combination of at least two of glucose, sucrose, citric acid, or polyethylene glycol.
8. The preparation method according to claim 6, characterized in that, The amount of organic carbon source added is 8wt%-14wt% of the theoretical amount of pure phase lithium iron phosphate generated.
9. The preparation method according to claim 1, characterized in that, In step (1), a dopant was also added during the mechanical grinding process.
10. The preparation method according to claim 9, characterized in that, The dopant includes any one or a combination of at least two of titanium dioxide, magnesium oxide, or vanadium pentoxide.
11. The preparation method according to claim 9, characterized in that, The amount of dopant added is 2wt‰-5wt‰ of the theoretical amount of pure-phase lithium iron phosphate to be generated.
12. The preparation method according to claim 1, characterized in that, The lithium source in the solid-phase raw material in step (1) includes lithium carbonate and / or lithium hydroxide.
13. The preparation method according to claim 1, characterized in that, The dispersion medium in step (1) includes deionized water.
14. The preparation method according to claim 1, characterized in that, In step (2), the mass of lithium iron phosphate generated from the liquid phase raw materials accounts for 85%-95% of the total mass of the lithium iron phosphate cathode material.
15. The preparation method according to claim 1, characterized in that, The lithium source in the liquid phase raw material in step (2) includes any one or a combination of at least two of lithium carbonate, lithium hydroxide, or lithium dihydrogen phosphate.
16. The preparation method according to claim 1, characterized in that, The drying method described in step (3) includes spray drying.
17. The preparation method according to claim 16, characterized in that, The inlet temperature of the spray dryer is 180℃-280℃, and the outlet air temperature is 80℃-110℃.
18. The preparation method according to claim 1, characterized in that, The heating rate of the sintering in step (3) is 2℃ / min-5℃ / min, the temperature is 700℃-820℃, and the time is 6h-10h.
19. The preparation method according to claim 1, characterized in that, After sintering in step (3), the material was crushed and sieved.
20. The preparation method according to claim 1, characterized in that, The preparation method includes the following steps: (1) The solid-phase raw materials, organic carbon source, dopant and dispersion medium are stirred and dispersed to obtain a slurry with a solid content of 40wt%-60wt%, and then sand milled until the particle size D50 is 1.2μm-1.8μm to obtain the first slurry; The mass of lithium iron phosphate generated from the solid-phase raw materials accounts for 5%-15% of the total mass of the lithium iron phosphate cathode material; the amount of organic carbon source added is 8wt%-14wt% of the theoretical amount of pure phase lithium iron phosphate generated; the amount of dopant added is 2wt‰-5wt‰ of the theoretical amount of pure phase lithium iron phosphate generated. (2) After dissolving or dispersing the raw materials of the liquid phase method by stirring with a solvent, a second slurry is obtained. The first slurry of step (1) is added to the second slurry to obtain a third slurry. The mass of lithium iron phosphate produced from the liquid-phase raw materials accounts for 85%-95% of the total mass of the lithium iron phosphate cathode material; (3) The third slurry described in step (2) is spray-dried. The inlet temperature of the spray drying is 180℃-280℃ and the outlet temperature is 80℃-110℃ to obtain a composite precursor. Then, the composite precursor is heated to 700℃-820℃ under a protective gas at a heating rate of 2℃ / min-5℃ / min and sintered for 6h-10h. After cooling, crushing and sieving, the lithium iron phosphate cathode material is obtained.
Citation Information
Patent Citations
Preparation method for improving compaction density of lithium iron phosphate anode material and lithium iron phosphate anode material
CN109795998A
High-compaction-density lithium iron phosphate anode material and preparation method thereof
CN108011104A
